Does background color influence visual thresholds?. (November 2020) - Pérez, María M.; Della Bona, Alvaro; Carrillo-Pérez, Francisco; Dudea, Diana; Pecho, Oscar E.; Herrera, Luis Javier
Abstract: Objective: To evaluate the influence of neutral color backgrounds on visual thresholds using three color difference metrics: CIELAB, CIEDE2000(1:1:1) and CIEDE2000(2:1:1). Methods: Sixty observers (dentists and laypersons; n = 30) from three countries participated in the study. A psychophysical experiment based on visual assessments of simulated images of teeth on a calibrated display was performed. Images of simulated upper central incisors (SUCI) were consecutively displayed in pairs (60) on 3 neutral color backgrounds (black, grey and white). Three color difference metrics (CIELAB, CIEDE2000(1:1:1), and CIEDE2000(2:1:1)) were used to calculate the visual thresholds (PT- perceptibility threshold; and AT- acceptability threshold) with 95 % confidence intervals (CI) and a Takagi-Sugeno-Kang (TSK) Fuzzy Approximation model was used as fitting procedure. Data was statistically analyzed using paired t -test (p = 0.05). Results: The 50:50 % PT values were significantly lower over white background than over black background. The 50:50 % AT values were significantly greater over white background than over grey and black backgrounds. In most cases, the thresholds (PT and AT) values were significantly different for each color different metric over each background color (p ≤ 0.05). No difference was found between observers for PT and AT values. Conclusions: The perceptibility and acceptability thresholds in dentistry are affected by the color difference metrics and by the background color. Significance: Dental color mismatches are more difficult to be accepted over a white background.